(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2019)
The purpose of this work is to carry out a novel solution of the transient heat transfer problem in the start-up phase of direct-chill casting processes using a Generalized Finite Differences Method. This formulation is applied in order to solve the heat transfer equation in strong form under a Lagrangian description. The incorporation of the boundary conditions is done in a direct and simple manner. The meshfree nature of this approach gives the advantage of naturally capture the motion and phase boundaries evolution without the need of remeshing approaches. The simplicity, efficiency and suitability of this numerical formulation is demonstrated by comparison with published numerical results reported by other researchers which show that this approach is promising for simulating heat transfer problems during the start-up phase of direct-chill casting processes.